A Survey of USA Anesthesiology Residents Regarding Their Perceptions of, and Barriers to, Fellowship Training in Obstetric Anesthesia. Issue 2 (24th June 2022) - Ende, H.B.; Lozada, M.J.; Micevych, P.S.; Pennycuff, J.; Vadhera, R.B.; Peralta, F.M.; Bauchat, J.R.
Abstract : ( Int J Obstet Anesth . 2021;46:103159) There is a clear need for fellowship-trained obstetric anesthesiologists, who may improve maternal outcomes. However, far fewer residents are participating in obstetric fellowships than is needed to staff labor and delivery units in the United States. A recent survey aimed to understand reasons why residents lack interest in pursuing obstetric anesthesia fellowship training.